2007
DOI: 10.1007/s12032-007-0020-1
|View full text |Cite
|
Sign up to set email alerts
|

Cancer during pregnancy: 10-year experience at a regional cancer reference center in Mexico

Abstract: Cancer during pregnancy appears to have a worse outcome when compared to the results reported in the literature of non-pregnant women with the same conditions. This may be related to the advanced clinical stages we found. Cancer during pregnancy requires specialized attention to improve both fetal and maternal outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 16 publications
0
11
0
3
Order By: Relevance
“…The women diagnosed with PABC in this literature review were found to be between the ages of 20 to 53 19,22–24,27,28,30–32,34 . Women in their third decade of life were the largest group of women represented in current PABC research 2,19,24,27,28,31,35 .…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…The women diagnosed with PABC in this literature review were found to be between the ages of 20 to 53 19,22–24,27,28,30–32,34 . Women in their third decade of life were the largest group of women represented in current PABC research 2,19,24,27,28,31,35 .…”
Section: Resultsmentioning
confidence: 88%
“…Breast cancer was diagnosed in 502 women during pregnancy and in 1068 women during lactation or postpartum. Of the studies reviewed, there were three case control studies, 12,22,23 six retrospective case series, 19,24–28 two retrospective cohorts, 2,29 three retrospective cancer registry reviews, 30–32 and one correlational mathematical modeling study 33 . Three common themes were addressed in the studies: 1) maternal age and gestation at diagnosis, 2) delay in PABC diagnosis, and 3) metastasis (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Existen factores que favorecen el recrudecimiento de esta patología durante el embarazo, entre los cuales se pueden mencionar los siguientes: (a) la falta de un control prenatal en la mayoría de las mujeres embarazadas, (b) la baja cobertura en el programa de pesquisa del cáncer de cérvix, y (c) la resistencia del personal de salud a explorar a una mujer embarazada ante la falsa sensación de atribuir los signos y síntomas al propio embarazo (2). Este último, representa un problema importante para el diagnóstico, ya que con frecuencia no se hace durante el embarazo, porque a la hemorragia genital se le atribuye origen obstétrico y no se efectúa especuloscopia (8).…”
Section: Discussionunclassified
“…El cáncer es la segunda causa de muerte a nivel mundial en la etapa reproductiva de la mujer, presentándose con una incidencia de 0,02 a 0,1% de todos los embarazos (1). Se estima que 1/1.000 a 1/1.500 recién nacidos se han asociado a una neoplasia maligna materna (2,3).…”
Section: Introductionunclassified
See 1 more Smart Citation